Digitale vegar til Norsk Ordbok - Ellingsve, Eli Johanne (Nordiske Studier i Leksikografi, 2007)
In 2014, Norsk Ordbok will be complete in 12 volumes. At a time when more and more people are getting knowledge and information via the Internet it is natural to consider developing a digital version of the dictionary as well. A digital version will present the dictionary makers with opportunities as well as challenges. The digital version will make it possible to add audiovisual supplements to the traditional written presentation of entries.Coordination and possible synergy effects in relation to other digital media and the Internet will involve finding technological solutions and a strategic location. The lecture will consider two possible ways to address the location on the web. Linguistic adaptation and strategic thinking related to the use of New Norwegian are also elements which should be considered along the route towards a digital dictionary.